2018
DOI: 10.1101/502328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual exposure enhances stimulus encoding and persistence in primary cortex

Abstract: Sensory exposure alters the response properties of individual neurons in primary sensory cortices. However, it remains unclear how these changes affect stimulus encoding by populations of sensory cells. Here, recording from populations of neurons in cat primary visual cortex, we demonstrate that visual exposure enhances stimulus encoding and discrimination. We find that repeated presentation of brief, high-contrast shapes results in a stereotyped, biphasic population response consisting of a short-latency tran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…The prediction that priors stored in the network contribute to the stimulus specificity of substates is also supported by the finding that classifiers trained to identify stimuli often perform better on the delayed, reverberating part of the responses than on the initial transients that are dominated by direct sensory input (175). Principal component analysis (PCA) of the rate vectors showed that the segregation of the vectors induced by different stimuli can increase over a few hundred milliseconds even after stimulus offset (175).…”
Section: Predictions and Experimental Evidencementioning
confidence: 90%
See 3 more Smart Citations
“…The prediction that priors stored in the network contribute to the stimulus specificity of substates is also supported by the finding that classifiers trained to identify stimuli often perform better on the delayed, reverberating part of the responses than on the initial transients that are dominated by direct sensory input (175). Principal component analysis (PCA) of the rate vectors showed that the segregation of the vectors induced by different stimuli can increase over a few hundred milliseconds even after stimulus offset (175).…”
Section: Predictions and Experimental Evidencementioning
confidence: 90%
“…This interpretation is supported by simulations of self-organizing recurrent networks. If the recurrent connections are endowed with Hebbian synapses, they reproduce this improved classification of familiar stimuli (121,175,178). Direct evidence for unsupervised modifications of recurrent connections by repeated stimulation is also available from the cat visual cortex of anesthetized cats (166).…”
Section: Predictions and Experimental Evidencementioning
confidence: 96%
See 2 more Smart Citations
“…This limits inferences on the cellular origins of increased synchronization. Since different neurons may show different repetition effects, these could average out, potentially masking repetition-related increases or stability in firing rate for subsets of neurons (Homann et al, 2017; Lazar et al, 2018; Patterson et al, 2013; Solomon and Kohn, 2014; Wissig and Kohn, 2012). Notably, Brunet et al (2014) showed that putative interneurons increasingly synchronized with repetition, whereas poorly driven putative excitatory cells dropped out of the gamma-rhythm.…”
Section: Discussionmentioning
confidence: 99%